Proceedings of the 14th Conference of the European Chapter of the Association for Computational Linguistics, Volume 2: Short Pa 2014
DOI: 10.3115/v1/e14-4035
|View full text |Cite
|
Sign up to set email alerts
|

Some Experiments with a Convex IBM Model 2

Abstract: Using a recent convex formulation of IBM Model 2, we propose a new initialization scheme which has some favorable comparisons to the standard method of initializing IBM Model 2 with IBM Model 1. Additionally, we derive the Viterbi alignment for the convex relaxation of IBM Model 2 and show that it leads to better F-Measure scores than those of IBM Model 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, for IBM Model 2, the data breaks such symmetries, so any relaxation will be nontrivial. (Simion, Collins, and Stein 2013) introduced the first convex relaxation of a model beyond IBM Model 1, design an algorithm for its optimization, and showed that it gives the same level of performance as IBM Model 2 (Simion, Collins, and Stein 2014).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for IBM Model 2, the data breaks such symmetries, so any relaxation will be nontrivial. (Simion, Collins, and Stein 2013) introduced the first convex relaxation of a model beyond IBM Model 1, design an algorithm for its optimization, and showed that it gives the same level of performance as IBM Model 2 (Simion, Collins, and Stein 2014).…”
Section: Related Workmentioning
confidence: 99%
“…For one, we could find the optimal alignment for I2CR-4 using IBM Model 2's rule (this is the optimal rule for I2CR-3 as well). On the other hand, using the same methods as presented in (Simion, Collins, and Stein 2014) we can find the optimal vector a (k) by splitting the maximization over the components of a (k) and focusing on finding a…”
Section: Decoding With I2cr-3 and I2cr-4mentioning
confidence: 99%
See 1 more Smart Citation